(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
In this article, measures that should be taken to achieve the goals set during the national green space movement through the development of the cocoon business in the agricultural regions of our country have been considered. Using the opportunity of green small business through the development of the cocooning business in agriculture is the basis for great results, the possibility of eliminating unemployment and eliminating poverty was substantiated scientifically and practically through the analysis.